A Known Naphthalene, Isoeleutherol, from the Herb of Lygodium microphyllum - Kuncoro, Hadi; Farabi, Kindi; Rijai, Laode; Julaeha, Euis; Shiono, Yoshihito; Supratman, Unang (Makara Journal of Science, 2018)
A known naphthalene, isoeleutherol (1), was isolated from the herb ofLygodium microphyllum. The chemical structure of 1 was determined on the basis of spectroscopic data mainly UV, IR, HRTOFMS, 1D-and 2D-NMR spectroscopy, aswell as by comparing with compounds previously reported. Isoeleutherol was isolated from this plant for the first timeand showed moderate antioxidant activity against DPPH (2,2-diphenyl-1-picrylhydrazyl) with IC50 value of 53.96 ± 2.87 μg/mL.